Analysis of current-voltage characteristics of Fe/MgO/GaAs junctions using self-consistent field modeling - Park, Y. J.; Hickey, M. C.; Van Veenhuizen, M. J.; Chang, J.; Heiman, D.; Moodera, J. S. (AMER PHYSICAL SOC, 2009)
Current-voltage data in metal-insulator-semiconductor devices are usually interpreted by a model of the tunneling current or the Schottky thermionic emission current. In these models, the barrier through which the electrical current flows is normally assumed to be rectangular or at best trapezoidal. For metal-insulator-metal junctions, this is a reasonable assumption. However, when one electrode is a doped semiconductor, the parameters of the current-voltage models require a self-consistent field description and the bias-dependent band bending within the semiconductor must be taken into account. These bias-dependent energy-band profiles are modeled with a Schroumldinger-Poisson solver and incorporated into the fitting procedure for the current-voltage data. We find that the ratio of the Schottky thermionic emission to the tunneling current, as well as the tunnel barrier heights can be determined using this approach. With this approach, one can quantitatively distinguish between tunneling and thermionic transport regimes and this is particularly applicable to the interpretation of spin-transport experiments in metal-insulator-semiconductor devices.
Keywords: TUNNEL MOS DIODES; ROOM-TEMPERATURE; MGO; MAGNETORESISTANCE; INTERFACE